Biolasing from individual cells in a low-Q resonator enables spectral fingerprinting - Septiadi,D; Barna,V; Saxena,D; Sapienza,R; Genovese,D; De,Cola L (Advanced Optical Materials, 2020)
Lasing from cells has recently been subject of thorough investigation because of the potential for sensitive and fast biosensing. Yet, lasing from individual cells has been studied in highquality resonators, resulting in limited dependence of the lasing properties on the cellular microenvironment. Here, lasing is triggered by cells floating in a low quality factor resonator composed of a disposable poly(methyl methacrylate) (PMMA) cell countingslide, hence in absence of conventional highreflectivity optical cavities. The exceptional spectral narrowing and the steep slope increase in the input–output energy diagram prove occurrence of laser action in presence of cells. The observed biolasing is an intrinsically dynamic signal, with large fluctuations in intensity and spectrum determined by the optical properties of the individual cell passing through the pump beam. Numerical simulations of the scattering efficiency rule out the possibility of optical feedback from either WGM (whispering gallery mode) or multiple scattering within the cell, and point to the enhanced directional scattering field as the crucial contribution of cells to the laser action. Finally, principal component analysis of lasing spectra measured from freely diffusing cells yields spectral fingerprints of cell populations, which allows discriminating cancer from healthy Rattus glial cells with high degree of confidence.